PENGARUH INHALASI AROMATERAPI LEMON TERHADAP KELUHAN MUAL MUNTAH PADA IBU HAMIL TRIMESTER I DI KLINIK KARAWANG PERDANA HUSADA - Imelda Diana Marsilia; Nina Tresnayanti; Tuti Alawiyah (STIKES MITRA RIA HUSADA, 2022)
Nausea and vomiting or in medical language is called emesis gravidarum or moming sickness is a condition of nausea which is sometimes accompanied by vomiting (frequency less than 5 times). Although this condition usually stops in the first trimester, the symptoms can cause nutritional disturbances, dehydration, weakness, weight loss, and electrolyte imbalance, if this is not treated it can lead to hyperemesis gravidarum which is reported to occur in about 0.05-2% of all pregnancies. The purpose of this study was to determine the effect of inhalation of lemon aromatherapy on complaints of nausea and vomiting in first trimester pregnant women at the Karawang Perdana Husada Clinic. This type of research is quantitative with a Quasi-experimental design with one group pre test post test. The sample in this study amounted to 35 respondents, namely patients at the Clinic Karawang Perdana Husada who were determined by total sampling. The research data were collected using a questionnaire. Data analysis used bivariate (Sample T-test). The results showed that there was an effect between nausea anad vomiting with inhalation of lemon aromatherapy (p = 0.000). lemon can be recommended as an intervention in the obstetric care of pregnant women with emesis gravidarum.